Enhancing vehicle routing problem solutions through deep reinforcement learning and graph neural networks - Zhou Cien Tien; Joe Qi-lee (International Journal of Enterprise Modelling, 2022)
The Vehicle Routing Problem (VRP) involves finding optimal routes for a fleet of vehicles to serve a set of clients while minimizing costs or optimizing efficiency. Scalability and uncertainty handling are issues with traditional VRP solutions. This study integrates Deep Reinforcement Learning (RL) with Graph Neural Networks (GNNs) to improve VRP solutions. Deep RL algorithms let agents learn optimal decision-making rules by interacting with the environment, whereas GNNs capture the VRP's graph representation's spatial and structural relationships. This research uses deep RL and GNNs to improve VRP solutions. The project intends to create an agent that can reason about customer, vehicle, and depot interactions and make educated routing decisions depending on the problem state by integrating deep RL agents with GNN models. Formulating the problem, preprocessing the data, constructing state and action representations, defining reward functions, training the deep RL agent and GNN models, and assessing the proposed strategy using benchmark VRP datasets. The merged deep RL-GNN technique improves VRP solutions. Optimized routing reduces travel expenses, improves resource use, and boosts efficiency. This research shows how deep RL and GNNs can overcome the limits of classic optimization methods for vehicle routing optimization. The findings emphasize the need of integrating advanced machine learning techniques into the VRP domain, enabling more effective and scalable real-world vehicle routing systems